b - (NbAASANBAT d(B.s; (NmONGOL uLSYN iH sURGUULXs ((Nub(B.s, 2002)
(NdISs
(NdIS(B-165s
Keywords: (NH\L [INVL\Ls; (NHUU^IN MONGOL BI^IGs; (NUJGARVIN BI^IGs; (NMANV H\Ls; (NHARXCUULSAN H\L [INVL\Ls; (NDISSERTACIs